The Structure and Rhetorical Aim of Deut 4:32–40: The Blending of Historical, Universal, Sensorial and Relational motifs - Coetsee, Albert Johannes (Old Testament Essays, 2022)
Deuteronomy 4:32–40 is viewed by various scholars as the climax of Moses’ first speech. While the passage has received considerable discussion on literary-critical front and in terms of its theology, the structure of the passage hasn’t received the same amount of scholarly attention. The reason for the lack of analyses of the structure may be due to the fact that the structure of the passage seems quite simple (Deut 4:32–35, 36–39, 40). The question, however, that has not been adequately addressed, is why Deut 4:36–39 seems to repeat Deut 4:32–35 in part, and what can be deduced from this repetition. The article attempts to answer this question by investigating the occurrence of four primary themes found in the passage, namely historical, universal, sensorial and relational themes, each made up of various motifs. It is argued that the blending of these motifs indicate a deliberate development within the structure of the passage. The article concludes by reflecting on the multifaceted rhetorical aim of the passage in the light of its structure.